Symbolic Computation of Lax Pairs of Integrable Nonlinear Partial Difference Equations on Quad-Graphs Part I: Scalar Nonlinear Lattices Willy Hereman Department of Mathematical and Computer Sciences Colorado School of Mines Golden, Colorado, U.S.A. http://www.mines.edu/fs home/whereman/ Department of Statistics and Computer Sciences Kadir Has University, Istanbul, Turkey Friday, July 1, 2011, 14:00 Collaborators Prof. Reinout Quispel Dr. Peter van der Kamp La Trobe University, Melbourne, Australia Ph.D. student: Terry Bridgman (CSM) Research supported in part by NSF under Grant CCF-0830783 This presentation is made in TeXpower Part I Scalar Nonlinear Lattices Outline • What are nonlinear P∆Es? • Classification of integrable nonlinear P∆Es in 2D • Lax pairs of nonlinear PDEs • Lax pair of nonlinear P∆Es • Examples of Lax pair of nonlinear P∆Es (including systems) • Algorithm (Nijhoff 2001, Bobenko & Suris 2001) • Software demonstration • Additional examples • Conclusions and future work What are nonlinear P∆Es? • Nonlinear maps with two (or more) lattice points! Some origins: • I full discretizations of PDEs I discrete dynamical systems in 2 dimensions I superposition principle (Bianchi permutability) for Bäcklund transformations between 3 solutions (2 parameters) of a completely integrable PDE Example: discrete potential Korteweg-de Vries (pKdV) equation (un,m − un+1,m+1 )(un+1,m − un,m+1 ) − p2 + q 2 = 0 • Notation: u is dependent variable or field (scalar case) n and m are lattice points p and q are parameters • For brevity, (un,m , un+1,m , un,m+1 , un+1,m+1 ) = (x, x1 , x2 , x12 ) • Alternate notations (in the literature): ˆ (un,m , un+1,m , un,m+1 , un+1,m+1 ) = (u, ũ, û, ũ) (un,m , un+1,m , un,m+1 , un+1,m+1 ) = (u00 , u10 , u01 , u11 ) • discrete pKdV equation: (un,m − un+1,m+1 )(un+1,m − un,m+1 ) − p2 + q 2 = 0 −→ (x − x12 )(x1 − x2 ) − p2 + q 2 = 0 (un,m − un+1,m+1 )(un+1,m − un,m+1 ) − p2 + q 2 = 0 (x − x12 )(x1 − x2 ) − p2 + q 2 = 0 x2 = un,m+1 p q x = un,m x12 = un+1,m+1 q p x1 = un+1,m Classification of 2D nonlinear integrable P∆Es Adler, Bobenko, Suris (ABS) 2003, 2007 • Family of nonlinear P∆Es in two dimensions: Q(x, x1 , x2 , x12 ; p, q) = 0 • Assumptions (ABS, 2003): 1. Affine linear Q(x, x1 , x2 , x12 ; p, q) = a1 xx1 x2 x12 + a2 xx1 x2 + . . . + a14 x2 + a15 x12 + a16 2. Invariant under D4 (symmetries of square) Q(x, x1 , x2 , x12 ; p, q) = Q(x, x2 , x1 , x12 ; q, p) = σQ(x1 , x, x12 , x2 ; p, q) , σ = ±1 3. Consistency around the cube Superposition of Bäcklund transformations between 4 solutions x, x1 , x2 , x3 (3 parameters: p, q, k) x23 x123 x2 x3 q x x12 x13 k p x1 • Trick: Introduce a third lattice variable ` • View u as dependent on three lattice points: n, m, `. So, x = un,m −→ x = un,m,` • Moves in three directions: n → n + 1 over distance p m → m + 1 over distance q ` → ` + 1 over distance k (spectral parameter) • Require that the same lattice holds on front, bottom, and left face of the cube • Require consistency for the computation of x123 = un+1,m+1,`+1 x23 x123 x2 x3 q x x12 x13 k p x1 Verification of Consistency Around the Cube Example: discrete pKdV equation ? Equation on front face of cube: (x − x12 )(x1 − x2 ) − p2 + q 2 = 0 Solve for x12 = x − Compute x123 : p2 −q 2 x1 −x2 x12 −→ x123 = x3 − p2 −q 2 x13 −x23 ? Equation on floor of cube: (x − x13 )(x1 − x3 ) − p2 + k2 = 0 Solve for x13 = x − Compute x123 : p2 −k2 x1 −x3 x13 −→ x123 = x2 − p2 −k2 x12 −x23 ? Equation on left face of cube: (x − x23 )(x3 − x2 ) − k2 + q 2 = 0 Solve for x23 = x − Compute x123 : q 2 −k2 x2 −x3 x23 −→ x123 = x1 − q 2 −k2 x12 −x13 ? Verify that all three coincide: q 2 − k2 p2 − k 2 p2 − q 2 x123 = x1 − = x2 − = x3 − x12 − x13 x12 − x23 x13 − x23 Upon substitution of x12 , x13 , and x23 : x123 p2 x1 (x2 − x3 ) + q 2 x2 (x3 − x1 ) + k2 x3 (x1 − x2 ) = p2 (x2 − x3 ) + q 2 (x3 − x1 ) + k2 (x1 − x2 ) Consistency around the cube is satisfied! Tetrahedron property x123 p2 x1 (x2 − x3 ) + q 2 x2 (x3 − x1 ) + k2 x3 (x1 − x2 ) = p2 (x2 − x3 ) + q 2 (x3 − x1 ) + k2 (x1 − x2 ) is independent of x. Connects x123 to x1 , x2 and x3 . x23 x123 x2 x3 q x x12 x13 k p x1 Result of the ABS Classification • List H I (H1) (x − x12 )(x1 − x2 ) + q − p = 0 I (H2) (x−x12 )(x1 −x2 )+(q−p)(x+x1 +x2 +x12 )+q 2 −p2 = 0 I (H3) p(xx1 + x2 x12 ) − q(xx2 + x1 x12 ) + δ(p2 − q 2 ) = 0 • List A I (A1) p(x+x2 )(x1 +x12 )−q(x+x1 )(x2 +x12 )−δ 2 pq(p−q) = 0 I (A2) (q 2 − p2 )(xx1 x2 x12 + 1) + q(p2 − 1)(xx2 + x1 x12 ) −p(q 2 − 1)(xx1 + x2 x12 ) = 0 • List Q I (Q1) p(x−x2 )(x1 −x12 )−q(x−x1 )(x2 −x12 )+δ 2 pq(p−q) = 0 I (Q2) p(x−x2 )(x1 −x12 )−q(x−x1 )(x2 −x12 )+pq(p−q) (x+x1 +x2 +x12 )−pq(p−q)(p2 −pq+q 2 ) = 0 I (Q3) (q 2 −p2 )(xx12 +x1 x2 )+q(p2 −1)(xx1 +x2 x12 ) 2 δ −p(q 2 −1)(xx2 +x1 x12 )− (p2 −q 2 )(p2 −1)(q 2 −1)=0 4pq I (Q4) (mother) Hietarinta’s Parametrization sn(α + β; k) (x1 x2 + xx12 ) − sn(α; k) (xx1 + x2 x12 ) − sn(β; k) (xx2 + x1 x12 ) + sn(α; k) sn(β; k) sn(α + β; k)(1 + k2 xx1 x2 x12 ) = 0 where sn(α; k) is the Jacobi elliptic sine function with modulus k. I Other parametrizations (Adler, Nijhoff) are given in the literature. • (Q5) (universal case) Viallet 2010 a1 xx1 x2 x12 + a2 (xx2 x12 + x1 x2 x12 + xx1 x12 + xx1 x2 ) + a3 (xx1 + x2 x12 ) + a4 (xx12 + x1 x2 ) + a5 (x1 x12 + xx2 ) + a6 (x + x1 + x2 + x12 ) + a7 = 0 Lax Pair for Nonlinear PDEs – Operators • Historical example: Korteweg-de Vries equation ut + αuux + uxxx = 0 • Key idea: Replace the nonlinear PDE with a compatible linear system: ψxx + 16 αu − λ ψ = 0 ψt = −4ψxxx − αuψx − 21 αux ψ + a(t)ψ ψ is eigenfunction; λ is constant eigenvalue (λx = λt = 0). Lax Operators • Replace a completely integrable nonlinear PDE by Lψ = λψ ψt = Mψ • Require compatibility of both equations Hence, Lt ψ + Lψt = λψt Lt ψ + LMψ = λMψ = Mλψ = ˙ MLψ Lt ψ + (LM − ML)ψ = ˙ O • Lt + [L, M] = ˙ 0 Lax Equation: with commutator [L, M] = LM − ML, and where = ˙ means “evaluated on the PDE.” • Example: Lax operators for the KdV equation ∂2 α L= + uI 2 ∂x 6 ∂3 α ∂ ∂ M = −4 − u + u + A(t)I 3 ∂x 2 ∂x ∂x • Note: Lt ψ + [L, M]ψ = α 6 (ut + αuux + uxxx ) ψ Lax Pair for PDEs – Matrices (AKNS) • Express compatibility of Ψx = X Ψ Ψt = T Ψ ψ where Ψ = , φ • X and T are N × N matrices. Lax equation (zero-curvature equation): Xt − Tx + [X, T] = ˙ 0 with commutator [X, T] = XT − TX • Example: Lax matrices for KdV equation 0 1 X= λ − 16 αu 0 a(t) + 16 αux T= −4λ2 + 13 αλu + 1 2 2 α u 18 −4λ − 13 αu + 16 αu2x a(t) − 61 αux Lax pairs are not unique. A second Lax pair: 1 αu −ik 6 X̃ = −1 ik 3 + 1 iαku− 1 αu −4ik x 3 6 T̃ = −4k2 + 13 αu 1 2 u− 1 αu2 +iku − 1 u α 2k x 3 6 2 xx 4ik3 − 13 iαku+ 16 αux Equivalence under Gauge Transformations • Lax pairs are equivalent under a gauge transformation: If (X, T) is a Lax pair then so is (X̃, T̃) with X̃ = GXG−1 + Gx G−1 T̃ = GTG−1 + Gt G−1 G is arbitrary invertible matrix and Ψ̃ = GΨ. Thus, X̃t − T̃x + [X̃, T̃] = ˙ 0 • Example: For KdV equation X̃ = GXG−1 and T̃ = GTG−1 with −i k G= −1 where λ = −k2 . 1 0 Peter D. Lax (1926-) Lax Pair of Nonlinear P∆Es – Matrices (ABS) • • Replace the nonlinear P∆E by ψ1 = Lψ (recall ψ1 = ψn+1,m ) ψ2 = Mψ (recall ψ2 = ψn,m+1 ) f For scalar P∆Es, L, M are 2 × 2 matrices; ψ = g Express compatibility: ψ12 = L2 ψ2 = L2 Mψ ψ12 = M1 ψ1 = M1 Lψ • Lax equation: L2 M − M1 L = ˙ 0 Equivalence under Gauge Transformations • Lax pairs are equivalent under a gauge transformation If (L, M ) is a Lax pair then so is (L, M) with L = G1 LG−1 M = G2 MG−1 where G is non-singular matrix and φ = Gψ Proof: Trivial verification that (L2 M − M1 L) φ = 0 ↔ (L2 M − M1 L) ψ = 0 • Example 1: Discrete pKdV Equation (x − x12 )(x1 − x2 ) − p2 + q 2 = 0 • (H1) after p2 → p, q 2 → q Lax operators: x p2 − k2 − xx1 L = tLc = t 1 −x1 x q 2 − k2 − xx2 M = sMc = s 1 −x2 1 with t = s = 1 or t = √DetL = √ 21 2 c k −p 1 1 and s = √DetM = √ 2 2 . Here, tt2 ss1 = 1. c k −q • Note: L2 M − M1 L = (x − x12 )(x1 − x2 ) − with x p2 − k2 − xx1 L= 1 −x1 x q 2 − k2 − xx2 M = 1 −x2 −1 x1 + x2 N = 0 1 p2 + q2 N • Example 2: Discrete modified KdV Equation p(xx2 − x1 x12 ) − q(xx1 − x2 x12 ) = 0 • (H3) for δ = 0 and x → −x or x12 → −x12 Lax operators: −px kxx1 L = t k −px1 −qx kxx2 M = s k −qx2 with t = 1 x1 and s = 1 t = √DetL =√ c Note: t2 s t s1 = 1 , x2 1 (p2 −k2 )xx1 x x1 x x2 = or t = s = x1 , or 1 and s = √DetM =√ x1 . x2 c 1 (q 2 −k2 )xx2 Lax Pair Algorithm for Scalar P∆Es (Nijhoff 2001, Bobenko and Suris 2001) Applies to equations that are consistent on cube Example: Discrete pKdV Equation • Step 1: Verify the consistency around the cube Use the equation on floor (x − x13 )(x1 − x3 ) − p2 + k2 = 0 p2 −k2 x1 −x3 to compute x13 = x − = Use equation on left face x3 x−xx1 +p2 −k2 x3 −x1 (x − x23 )(x3 − x2 ) − k2 + q 2 = 0 to compute x23 = x − q 2 −k2 x2 −x3 = x3 x−xx2 +q 2 −k2 x3 −x2 x123 x23 x12 x2 q x13 x3 k x p x1 • Step 2: Homogenization ? Numerator and denominator of x13 = x3 x−xx1 +p2 −k2 x3 −x1 and x23 = x3 x−xx2 +q 2 −k2 x3 −x2 are linear in x3 . f g xf +(p2 −k2 −xx1 )g f −x1 g ? Substitute x3 = x13 = into x13 to get ? On the other hand, x3 = Thus, x13 = f1 g1 = f g −→ x13 = xf +(p2 −k2 −xx1 )g . f −x1 g Hence, f1 = t xf + g1 = t (f − x1 g) (p2 − k2 − xx1 )g and f1 . g1 ? In matrix form f1 x p2 − k2 − xx1 f = t g1 1 −x1 g f Matches ψ1 = Lψ with ψ = g f2 g2 xf +(q 2 −k2 −xx2 )g f −x2 g = ? Similarly, from x23 = f2 x q 2 − k2 − xx2 f = Mψ. ψ2 = = s 1 −x2 g g2 Therefore, x p2 − k2 − xx1 L = t Lc = t 1 −x1 x q 2 − k2 − xx2 M = s Mc = s 1 −x2 • Alternate method of deriving Lc and Mc ∂Q − ∂x −Q 2 L = t Lc = t ∂2Q ∂Q ∂x2 ∂x12 ∂x12 x2 =x12 =0 x p2 − k2 − xx1 = t 1 −x1 where t(x, x1 ; p, k), and Q(x, x1 , x2 , x12 ; p, k) = (x − x12 )(x1 − x2 ) − p2 + k2 = 0 • Apply x1 → x2 , p → q; s = t(x, x2 ; q, k) x q 2 − k2 − xx2 M = s Mc = s 1 −x2 • Step 3: Determine t and s ? Substitute L = tLc , M = sMc into L2 M − M1 L = 0 −→ t2 s(Lc )2 Mc − s1 t(Mc )1 Lc = 0 ? Solve the equation from the (2-1)-element for t2 s t s1 = f (x, x1 , x2 , p, q, . . . ) ? If f factors as F (x, x1 , p, q, . . .)G(x, x1 , p, q, . . .) f = F (x, x2 , q, p, . . .)G(x, x2 , q, p, . . .) then try t = F (x,x1 1 ,...) or s = F (x,x1 2 ,...) or 1 G(x,x1 ,...) 1 G(x,x2 ,...) −→ No square roots needed! and Works for the following lattices: mKdV, (H3) with δ = 0, (Q1), (Q3) with δ = 0, (α, β)-equation. Does not work for (A1) and (A2) equations! Needs further investigation! ? If f does not factor, apply determinant to get s s t2 s det Lc det (Mc )1 = t s1 det (Lc )2 det Mc ? A solution: t = √ 1 , det Lc s= √ 1 det Mc −→ Always works but introduces square roots! How to avoid square roots? Remedy: Apply a change of variables x = F (X) t2 s t s1 = f (F (X), F (X1 ), F (X2 ), p, q, . . . ) = F (X, X1 , p, q, . . .)G(X, X1 , p, q, . . .) F (X, X2 , q, p, . . .)G(X, X2 , q, p, . . .) Example 1: (Q2) Lattice q (x − x1 )2 − 2p2 (x + x1 ) + p4 t2 s = 2 2 4 t s1 p (x − x2 ) − 2q (x + x2 ) + q 2 2 2 2 q (X + X1 ) − p (X − X1 ) − p = 2 2 2 2 p (X + X2 ) − q (X − X2 ) − q setting x = F (X) = X 2 . Hence, x1 = X1 2 , x2 = X2 2 . Example 2: (Q3) Lattice t2 s q(q 2 −1) 4p2 (x2 +x21 )−4p(1+p2 )xx1 +δ 2 (1−p2 )2 = 2 2 2 2 2 2 2 2 t s1 p(p −1) 4q (x +x2 )−4q(1+q )xx2 +δ (1−q ) Set x = F (X) = δ cosh(X) then 4p2 (x2 +x21 )−4p(1+p2 )xx1 +δ 2 (1−p2 )2 = δ 2 (p−eX+X1 )(p−e−(X+X1 ) )(p−eX−X1 )(p−e−(X−X1 ) ) = δ 2 (p−cosh(X + X1 )+sinh(X + X1 )) (p−cosh(X + X1 )−sinh(X + X1 )) (p−cosh(X − X1 )+sinh(X − X1 )) (p−cosh(X − X1 )−sinh(X − X1 )) Software Demonstration Additional Examples • Example 3: (H1) Equation (ABS classification) (x − x12 )(x1 − x2 ) + q − p = 0 • Lax operators: x p − k − xx1 L = t 1 −x1 x q − k − xx2 M = s 1 −x2 with t = s = 1 or t = Note: t2 s t s1 = 1. √1 k−p and s = √1 k−q • Example 4: (H2) Equation (ABS 2003) (x−x12 )(x1 −x2 )+(q−p)(x+x1 +x2 +x12 )+q 2 −p2 = 0 • Lax operators: p − k + x p2 − k2 + (p − k)(x + x1 ) − xx1 L = t 1 −(p − k + x1 ) q − k + x q 2 − k2 + (q − k)(x + x2 ) − xx2 M = s 1 −(q − k + x2 ) 1 2(k−p)(p+x+x1 ) p+x+x1 t2 s = . t s1 q+x+x2 with t = √ Note: and s = √ 1 2(k−q)(q+x+x2 ) • Example 5: (H3) Equation (ABS 2003) p(xx1 + x2 x12 ) − q(xx2 + x1 x12 ) + δ(p2 − q 2 ) = 0 • Lax operators: kx − δ(p2 − k2 ) + pxx1 L = t p −kx1 kx − δ(q 2 − k2 ) + qxx2 M = s q −kx2 1 (p2 −k2 )(δp+xx1 ) δp+xx1 t2 s = . t s1 δq+xx2 with t = √ Note: and s = √ 1 (q 2 −k2 )(δq+xx2 ) • Example 6: (H3) Equation (δ = 0) (ABS 2003) p(xx1 + x2 x12 ) − q(xx2 + x1 x12 ) = 0 • Lax operators: kx −pxx1 L = t p −kx1 kx −qxx2 M = s q −kx2 with t = s = x1 or t = x11 and s = Note: tt2 ss1 = xx xx12 = xx12 . 1 x2 • • Example 7: (Q1) Equation (ABS 2003) p(x−x2 )(x1 −x12 )−q(x−x1 )(x2 −x12 )+δ 2 pq(p−q) = 0 Lax operators: (p − k)x1 + kx −p δ 2 k(p − k) + xx1 L = t p − (p − k)x + kx1 (q − k)x2 + kx −q δ 2 k(q − k) + xx2 M = s q − (q − k)x + kx2 1 1 with t = δp±(x−x and s = , δq±(x−x2 ) 1) 1 and or t = q k(p−k)((δp+x−x1 )(δp−x+x1 )) 1 s= q k(q−k)((δq+x−x2 )(δq−x+x2 )) Note: t2 s t s1 = q (δp+(x−x1 ))(δp−(x−x1 )) p(δq+(x−x2 ))(δq−(x−x2 )) . • Example 8: (Q1) Equation (δ = 0) (ABS 2003) p(x − x2 )(x1 − x12 ) − q(x − x1 )(x2 − x12 ) = 0 which is the cross-ratio equation (x − x1 )(x12 − x2 ) p = (x1 − x12 )(x2 − x) q • Lax operators: (p − k)x1 + kx −pxx1 L = t p − (p − k)x + kx1 (q − k)x2 + kx −qxx2 M =s q − (q − k)x + kx2 Here, t2 s t s1 or t = √ = q(x−x1 )2 . p(x−x2 )2 1 k(k−p)(x−x1 ) So, t = 1 x−x1 and s = √ and s = 1 . k(k−q)(x−x2 ) 1 x−x2 • Example 9: (Q2) Equation (ABS 2003) p(x−x2 )(x1 −x12 )−q(x−x1 )(x2 −x12 )+pq(p−q) (x+x1 +x2 +x12 )−pq(p−q)(p2 −pq+q 2 ) = 0 • Lax operators: (k−p)(kp−x1 )+kx 2 2 L = t −p k(k−p)(k −kp+p −x−x1 )+xx1 p − (k−p)(kp−x)+kx1 (k−q)(kq−x2 )+kx 2 2 M = s −q k(k−q)(k −kq+q −x−x2 )+xx2 q − (k−q)(kq−x)+kx2 • with t= 1 q k(k−p)((x−x1 )2 −2p2 (x+x1 )+p4 ) and s= 1 q k(k−q)((x−x2 )2 −2q 2 (x+x2 )+q 4 ) Note: t2 s t s1 = = )2 2p2 (x p4 q (x − x1 − + x1 ) + p (x − x2 )2 − 2q 2 (x + x2 ) + q 4 2 2 2 2 p (X + X1 ) − p (X − X1 ) − p 2 2 2 2 q (X + X2 ) − q (X − X2 ) − q with x = X 2 , and, consequently, x1 = X12 , x2 = X22 . • Example 10: (Q3) Equation (ABS 2003) (q 2 −p2 )(xx12 +x1 x2 )+q(p2 −1)(xx1 +x2 x12 ) 2 δ −p(q 2 −1)(xx2 +x1 x12 )− (p2 −q 2 )(p2 −1)(q 2 −1) = 0 4pq • Lax operators: −4kp p(k2 −1)x+(p2 −k2 )x1 2 2 2 2 4 2 2 2 2 2 2 L = t −(p −1)(δ k −δ k −δ p +δ k p −4k pxx1 ) −4k2 p(p2 −1) 4kp p(k2 −1)x1 +(p2 −k2 )x −4kq q(k2 −1)x+(q 2 −k2 )x2 2 2 2 2 4 2 2 2 2 2 2 M= s −(q −1)(δ k −δ k −δ q +δ k q −4k qxx2 ) −4k2 q(q 2 −1) 4kq q(k2 −1)x2 +(q 2 −k2 )x • with t= 1 q 2k p(k2−1)(k2−p2 )(4p2 (x2 +x21 )−4p(1+p2 )xx1 +δ 2 (1−p2 )2 ) and 1 s= 2k q q(k2−1)(k2−q 2 )(4q 2 (x2 +x22 )−4q(1+q 2 )xx2 +δ 2 (1−q 2 )2 ) . Note: t2 s t s1 2 2 2 2 2 2 2 2 q(q −1) 4p (x +x1 )−4p(1+p )xx1 +δ (1−p ) = 2 p(p2 −1) 4q 2 (x2 +x2 )−4q(1+q 2 )xx2 +δ 2 (1−q 2 )2 2 2 2 2 2 2 2 q(q −1) 4p (x−x1 ) −4p(p−1) xx1 +δ (1−p ) = p(p2 −1) 4q 2 (x−x2 )2 −4q(q−1)2 xx2 +δ 2 (1−q 2 )2 2 2 2 2 2 2 2 q(q −1) 4p (x+x1 ) −4p(p+1) xx1 +δ (1−p ) = 2 2 2 2 2 2 2 p(p −1) 4q (x+x2 ) −4q(q+1) xx2 +δ (1−q ) where 4p2 (x2 +x21 )−4p(1+p2 )xx1 +δ 2 (1−p2 )2 = δ 2 (p−eX+X1 )(p−e−(X+X1 ) )(p−eX−X1 )(p−e−(X−X1 ) ) = δ 2 (p−cosh(X + X1 )+sinh(X + X1 )) (p−cosh(X + X1 )−sinh(X + X1 )) (p−cosh(X − X1 )+sinh(X − X1 )) (p−cosh(X − X1 )−sinh(X − X1 )) with x = δ cosh(X), and, consequently, x1 = δ cosh(X1 ), x2 = δ cosh(X2 ). • Example 11: (Q3) Equation (δ) = 0 (ABS 2003) (q 2 − p2 )(xx12 + x1 x2 ) + q(p2 − 1)(xx1 + x2 x12 ) −p(q 2 − 1)(xx2 + x1 x12 ) = 0 • Lax operators: (p2 −k2 )x1 +p(k2 −1)x −k(p2 −1)xx1 L = t (p2 −1)k − (p2 −k2 )x+p(k2 −1)x1 (q 2 −k2 )x2 +q(k2 −1)x −k(q 2 −1)xx2 M = s (q 2 −1)k − (q 2 −k2 )x+q(k2 −1)x2 • with t = or t = 1 px−x1 1 px1 −x or t = √ and s = 1 qx−x2 1 qx2 −x 1 (k2 −1)(p2 −k2 )(px−x1 )(px1 −x) and s = √ Note: and s = 1 . 2 2 2 (k −1)(q −k )(qx−x2 )(qx2 −x) t2 s t s1 = (q 2 −1)(px−x1 )(px1 −x) . (p2 −1)(qx−x2 )(qx2 −x) • Example 12: (α, β)-equation (Quispel 1983) (p−α)x−(p+β)x1 (p−β)x2 −(p+α)x12 − (q−α)x−(q+β)x2 (q−β)x1 −(q+α)x12 = 0 • Lax operators: (p−α)(p−β)x+(k2−p2 )x1 −(k−α)(k−β)xx1 L = t (k+α)(k+β) − (p+α)(p+β)x1 +(k2−p2 )x (q−α)(q−β)x+(k2−q 2 )x2 −(k−α)(k−β)xx2 M = s (k+α)(k+β) − (q+α)(q+β)x2 +(k2−q 2 )x • with t = 1 (α−p)x+(β+p)x1 ) or t = 1 (β−p)x+(α+p)x1 ) or t = q and s = 1 (α−q)x+(β+q)x2 ) 1 (β−q)x+(α+q)x2 ) 1 and s = Note: and s = (p2 −k2 )((β−p)x+(α+p)x1 )((α−p)x+(β+p)x1 ) 1 q (q 2 −k2 )((β−q)x+(α+q)x2 )((α−q)x+(β+q)x2 ) t2 s t s1 ((β−p)x+(α+p)x1 )((α−p)x+(β+p)x1 ) = (β−q)x+(α+q)x (α−q)x+(β+q)x . ( 2 )( 2) • Example 13: (A1) Equation (ABS 2003) p(x+x2 )(x1 +x12 )−q(x+x1 )(x2 +x12 )−δ 2 pq(p−q) = 0 • (Q1) if x1 → −x1 and x2 → −x2 Lax operators: (k − p)x1 + kx −p δ 2 k(k − p) + xx1 L = t p − (k − p)x + kx1 (k − q)x2 + kx −q δ 2 k(k − q) + xx2 M = s q − (k − q)x + kx2 • with t = s= q Note: 1 q k(k−p)((δp+x+x1 )(δp−x−x1 )) 1 and k(k−q)((δq+x+x2 )(δq−x−x2 )) t2 s t s1 = q (δp+(x+x1 ))(δp−(x+x1 )) p(δq+(x+x2 ))(δq−(x+x2 )) However, the choices t = . 1 δp±(x+x1 ) and s = cannot be used. Needs further investigation! 1 δq±(x+x2 ) • Example 14: (A2) Equation (ABS 2003) (q 2 − p2 )(xx1 x2 x12 + 1) + q(p2 − 1)(xx2 + x1 x12 ) −p(q 2 − 1)(xx1 + x2 x12 ) = 0 (Q3) with δ = 0 via Möbius transformation: x → x, x1 → • 1 , x2 x1 → 1 , x12 x2 → x12 , p → p, q → q Lax operators: k(p2 −1)x − p2 −k2 +p(k2 −1)xx1 L = t p(k2 −1)+(p2 − k2 )xx1 −k(p2 −1)x1 k(q 2 −1)x − q 2 −k2 +q(k2 −1)xx2 M = s q(k2 −1)+(q 2 −k2 )xx2 −k(q 2 −1)x2 • with t = √ and s = √ Note: 1 (k2 −1)(k2 −p2 )(p−xx1 )(pxx1 −1) 1 (k2 −1)(k2 −q 2 )(q−xx2 )(qxx2 −1) t2 s t s1 = (q 2 −1)(p−xx1 )(pxx1 −1) . (p2 −1)(q−xx2 )(qxx2 −1) However, the choices t = or t = 1 pxx1 −1 and s = 1 p−xx1 and s = 1 q−xx2 1 qxx2 −1 cannot be used. Needs further investigation! • Example 15: Discrete sine-Gordon Equation xx1 x2 x12 − pq(xx12 − x1 x2 ) − 1 = 0 (H3) with δ = 0 via extended Möbius transformation: x → x, x1 → x1 , x2 → • 1 , x12 x2 → − x112 , p → p1 , q → q Discrete sine-Gordon equation is NOT consistent around the cube, but has a Lax pair! Lax operators: qx2 1 p −kx1 − kx L= M = x px1 x2 − xk − q x k Conclusions and Future Work • Mathematica code works for scalar P∆Es in 2D defined on quad-graphs (quadrilateral faces). • Mathematica code has been extended to systems of P∆Es in 2D defined on quad-graphs. • Code can be used to test (i) consistency around the cube and compute or test (ii) Lax pairs. • Consistency around cube =⇒ P∆E has Lax pair. • P∆E has Lax pair ; consistency around cube. Indeed, there are P∆Es with a Lax pair that are not consistent around the cube. Example: Discrete sine-Gordon equation. • Avoid the determinant method to avoid square roots! Factorization plays an essential role! • Hard cases: Q4 equation (elliptic curves, Weierstraß functions) (Nijhoff 2001) and Q5 • Future Work: Extension to more complicated systems of P∆Es. • P∆Es in 3D: Lax pair will be expressed in terms of tensors. Consistency around a “hypercube”. Examples: discrete Kadomtsev-Petviashvili (KP) equations. Thank You